Justified. The complete final season [videorecording (DVD)] - Olyphant, Timothy; Searcy, Nick; Carter, Joelle
Raylan sets out to find out more about the mysterious group buying up land in Harlan, Boyd tries to make a profit off the ledger from the bank heist, and Ava is stuck in the middle of everything.